Development of a biosensor for phosphorylated Tau 181 protein detection in early-stage Alzheimers disease - Schneider, Maria (2022)
Alzheimer's disease (AD) is the most common form of dementia in the elderly, and there are still no reliable methods for its early detection. Recently, the phosphorylated protein Tau181 (p-Tau181) was identified as a highly specific biomarker for AD. Therefore, in this work, a new strategy for the development of an electrochemical-based immunosensor for the detection of p-Tau is described. For this purpose, a carbon screen-printed electrode (C-SPE) was modified with platinum nanoparticles decorated with multi-walled carbon nanotubes (MWCNTs- PAH /Pt) to enable antibody binding. Scanning electron microscopy, transmission electron microscopy, Raman and X-ray photoelectron spectroscopy were used to study the morphology and crystallinity of the nanomaterials. Cyclic voltammetry and square-wave voltammetry were performed to compare the electrochemical properties of these electrodes. Under optimal conditions, the developed immunosensor exhibited a linear range from 8.6 to 1100 pg/mL, and the detection limit was estimated to be 0.24 pg/mL. This device showed excellent reproducibility and stability with remarkable selectivity for p-Tau181 in serum samples. Overall, this device enables minimally invasive clinical evaluation of p-Tau181 level with high sensitivity through simple operation, which makes this device a promising tool for future point-of-care purposes that will contribute to the technological development of clinical diagnostics.